Inflasi, Tingkat Suku Bunga dan Return Saham Pada Masa Pandemi Covid-19 - Darminta, I Wayan Ananta Dharma; Sari, Maria Mediatrix Ratna (E-Jurnal Akuntansi; Vol 34 No 10 (2024), 2024)
The purpose of this study was to determine the effect of inflation and interest rates on stock returns during the covid-19 pandemic. This research was conducted in all corporate sectors listed on the Indonesia Stock Exchange during the 2019-2021 period. The number of samples to be taken is 254 companies using proportionate stratified random sampling technique. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis it was found that inflation had no effect on stock returns and interest rates had a negative effect on stock returns. Thus, it can be concluded that high or low inflation does not affect the rise and fall of stock returns and an increase in interest rates will cause a decrease in stock returns for companies on the Indonesia Stock Exchange in 2019-2021.